Developing Policies to Address Historic Contract Cheating and Misuse of Generative Artificial Intelligence - Lancaster, Thomas; Glendinning, Irene; Dann, Sandie; Crockett, Robin; Draper, Michael (Journal of Academic Writing, 2025)
When students submit written assignments for assessment, they are generally trusted to have completed these honestly, and to have benefitted from the opportunity to learn. Academic integrity breaches are sometimes detected during the assessment process. Some common examples of integrity breaches during students’ academic writing include contract cheating, the unauthorised use of GenAI technology for completing assignments, and using AI tools to disguise existing work so that it appears to be original. None of these are new phenomena. Processes and procedures should be in place for managing suspected academic misconduct cases detected during the assessment process. But what happens when academic misconduct is detected retrospectively, sometimes after a student has moved degree programmes or graduated? This position paper sets out the case for universities and other academic institutions having procedures in place to deal with historic academic misconduct. It provides examples of how institutions can become aware of misconduct, including through whistleblowing and through development of more effective detection software. The authors bring together legal and educational expertise to suggest considerations that individual institutions should make towards future policy development. The discussion considers that students must be supported and prepared for success, but that institutions cannot ignore the reputational risks associated with cases of historic misconduct.